2009
DOI: 10.1002/mds.22108
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease is overdiagnosed clinically at baseline in diagnostically uncertain cases: A 3‐year European multicenter study with repeat [123I]FP‐CIT SPECT

Abstract: Overdiagnosis of Parkinson's disease (PD) is suggested by specialist review of community diagnosis, and in postmortem studies. In specialist centers 4 to 15% of patients entered into clinical trials as early PD do not have functional imaging support for a PD diagnosis. In a European multicenter, prospective, longitudinal study, we compared clinical diagnosis with functional SPECT imaging using [123I]FP-CIT (DaTSCAN, GE Healthcare). Repeat observations were performed over 3 years in patients with tremor and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 27 publications
(35 reference statements)
9
127
0
10
Order By: Relevance
“…A similar conclusion was reached by investigators participating in a European multicenter, prospective, longitudinal study in which clinical diagnosis was compared with 123 I-FP-CIT SPECT findings (38). Serial observations were performed over 3 y on patients in whom there was initial diagnostic uncertainty between degenerative parkinsonism and a benign tremor disorder.…”
Section: Imaging Presynaptic Dopaminergic Function In Pdmentioning
confidence: 74%
“…A similar conclusion was reached by investigators participating in a European multicenter, prospective, longitudinal study in which clinical diagnosis was compared with 123 I-FP-CIT SPECT findings (38). Serial observations were performed over 3 y on patients in whom there was initial diagnostic uncertainty between degenerative parkinsonism and a benign tremor disorder.…”
Section: Imaging Presynaptic Dopaminergic Function In Pdmentioning
confidence: 74%
“…lack of specificity of signs and symptoms in the early stages of the disease (1,2). In some clinical situations, definitive diagnosis is only possible through postmortem neuropathology, and all in-life diagnoses are probable.…”
mentioning
confidence: 99%
“…Other studies are also reported a high interobserver agreement for visual analysis when using only a dichotomous division of normal versus abnormal SPECT images [22,23]. All of the patients with the clinical diagnosis of PS were visually classified as abnormal by both observers, therefore none of our patients could be considered as so-called SWEDD (Scans Without Evidence of Dopaminergic Deficit) patient; a small specific entity of patients clinically diagnosed with Parkinson's disease but having normal DAT imaging [22].…”
Section: Discussionmentioning
confidence: 68%